Biomarkers to assess an anti-inflammatory treatment for irritable bowel syndrome: mast cell assays and magnetic resonance imaging - Lam, Ching Yin (2015)
Irritable bowel syndrome (IBS) remains a heterogeneous condition and is a common condition. The causes of IBS remain poorly understood and there is a lack in biomarkers to distinguish this condition.